Catalogue of amphibian types in the collection of the Zoological Survey of India - Chanda, Shyamal Kumar; Das, I.; Dubois, Alain (Centre for Herpetology, Madras Crocodile Bank Trust, 2000)
The amphibian types in the collection of the National Zoological Collection, maintained by the Zoological Survey of India (ZSI), Kolkata (Calcutta), as well as those held by the regional stations at Dehra Dun and Chennai, are listed, up to 1 September 2000. The list includes many historical specimens collected and/or described by pioneering European naturalists, including Edward Blyth, Thomas Jerdon, William Blanford, William Theobald, Ferdinand Stoliczka, Nelson Annandale, and John Anderson, as well as those more recently described from expeditions to the Nicobar Islands, Arunachal Pradesh and Kerala, by the staff of the ZSI during the present century. The annotated list includes original citations, registration numbers, nature of types, and present status of every taxon. Additional remarks are provided where necessary. A total of 346 type specimens of amphibians are represented, including those representing 105 anuran species, one caudate species and nine apodan species, from Pakistan, India, Sri Lanka, Myanmar, China, Malaysia, and Indonesia. Syntypes from the original type series of two name-bearing taxa have lost their type status through the designation of lectotypes. In addition, the types of 39 name-bearing taxa described by the staff and members of the Asiatic Society of Bengal cannot be located in the ZSI collection.